CO2 from direct air capture as carbon feedstock for Fischer-Tropsch chemicals and fuels: Energy and economic analysis. Issue 46 (April 2021) - Marchese, Marco; Buffo, Giulio; Santarelli, Massimo; Lanzini, Andrea
Graphical abstract: Highlights: 5 layouts of a Fischer-Tropsch unit integrated with Direct air capture are studied. An electrified high temperature DAC solution is investigated. Up to 68.3 % of CO2 captured from ambient air is converted to FT hydrocarbons. The cost of wax production is 5.05–9.0 €/kgwax in the best plant configuration. Abstract: The investigated plant concept integrates the direct air capture technology with the Fischer-Tropsch synthesis. 250 kt/h of air, with a CO2 concentration of 400 ppm, are used as feedstock to produce the synthetic hydrocarbons. The direct air capture is modelled as a high-temperature calcium recovery loop process. An alkaline electrolyser and a reverse water-gas shift reactor produce the required syngas. The Fischer-Tropsch products distribution is described by a carbide model developed for a Co-Pt/ɣAl2 O3 catalyst for alkanes and alkenes of carbon number C1 -C70 . Five integration scenarios are analysed. In the base case, the energy demand of the direct air capture process is supplied with natural gas from the distribution grid. In improved configurations, the effect of Fischer-Tropsch off-gas recirculation to the reverse water-gas shift and/or the direct air capture units is explored, excluding the need of fossil fuel. An electrified direct air capture solution is also included. In the analysed scenarios, the highest system efficiency corresponds to 36.3 %, while the maximum carbon dioxide conversion is of 68.3 %. The maximum waxes production corresponds to 8.7 t/h. Lastly, capital and operating plant costs are allocated in an economic investigation, considering different market electricity costs and financial risk values. In a medium financial risk scenario (interest rate: 7.5 %), the minimum Fischer-Tropsch waxes production cost corresponds to 6.3 €/kgwax, reaching 5.05 €/kgwax at an interest rate of 0%. Lastly, the effect of learning curves over the production cost at the year 2030 and 2050 is included.